Evaluation Of Antibiotic Therapy Among Patients With Community-Acquired Pneumonia In Hospital Pulau Pinang - Primadiamanti, Annisa (2013)
Community-acquired pneumonia (CAP) is one of infectious diseases that cause morbidity and mortality, especially in Asia-Pacific regions. Antibiotics guideline is needed in order to achieve appropriate use of antibiotics for CAP management, including Malaysia. Outcome of therapy still needed to be monitored to evaluate the antibiotics use for hospitalized patients with CAP. Therefore, this study was aimed to evaluate antibiotics use for community-acquired pneumonia (CAP) in medical ward of Hospital Pulau Pinang, Malaysia.